2007
DOI: 10.32398/cjhp.v5i3.1246
|View full text |Cite
|
Sign up to set email alerts
|

College Women’s Perception and Knowledge of Human Papillomavirus (HPV) and Cervical Cancer

Abstract: Human papillomavirus (HPV) infections are one of the most common types of sexually transmitted infections in the United States. The highest rates of HPV infection are found in adult’s ages 18-28 years. This study utilizes the Health Belief Model to assess knowledge and perception of HPV infection and cervical cancer in college-age women and their intent to reduce their numbers of sex partners and request that their partner wear a condom during their next sexual encounter to prevent HPV infection. Even though m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 19 publications
2
23
0
4
Order By: Relevance
“…A sample size of 400 students was obtained using the hypothesis testing method (Lwanga and Lemeshow 1991) and based on the following assumptions; 95% confidence level, findings from a previous study (Lopez and McMahan 2007) and a 5% margin of error. The calculated minimum sample was increased by 10% to account for anticipated subject non-response.…”
Section: Study Design and Samplementioning
confidence: 99%
“…A sample size of 400 students was obtained using the hypothesis testing method (Lwanga and Lemeshow 1991) and based on the following assumptions; 95% confidence level, findings from a previous study (Lopez and McMahan 2007) and a 5% margin of error. The calculated minimum sample was increased by 10% to account for anticipated subject non-response.…”
Section: Study Design and Samplementioning
confidence: 99%
“…These studies provide important insights, but they focused primarily on European American and African-American college samples; none have drawn exclusively from Hispanic college samples (Lopez &, McMahan, 2007; Munoz et al, 2010; Sandfort & Pleasant, 2009; Winer et al, 2003). Similarly, Hispanic community-based samples do not capture the unique college contextual experiences that put these women at risk.…”
Section: Social Network Theorymentioning
confidence: 99%
“…The vaccination of college-age women against human papillomavirus (HPV) infection is a critical public health goal given that 50% of college women are estimated to be infected (Lopez & McMahan, 2007; Sandfort & Pleasant, 2009; Winer et al, 2003). It is important to consider the sources of information about vaccination used by college women as research has identified specific post-secondary school sexual contexts and values that often increase women’s risk for HPV transmission.…”
mentioning
confidence: 99%
“…The Health Belief Model (HBM) is one of the major conceptual frameworks guiding current research related to cancer screening [18]. However, few studies have used the HBM as a theoretical framework when examining the health beliefs unique to Hispanic women relative to cervical cancer and to cervical cancer screening and none of those studies have included cultural predictors for screening participation in their model [19][20][21][22][23].The purpose of this study was to utilize the HBM to determine South Carolina Upstate Hispanic women's cervical cancer screening behavior by examining selected cervical cancer and screening beliefs, Perceived Threats (i.e., susceptibility plus severity), Benefits, Barriers, and their degree of selfefficacy. In addition, how selected ''Cues to Action'' (e.g., media or a doctor's reminder note), and modifiers (e.g., socio-demographic, socio-economic, and cultural predictors) influenced their perceptions and thus their cervical cancer screening compliance within national guidelines.…”
Section: Introductionmentioning
confidence: 99%